USING HANGMAN GAME STRATEGY TO IMPROVE STUDENTS, READING COMPREHENSION ACHIEVEMENT - Ratnanery Ratnanery (Faculty of Teacher Training and Education, Universitas Sriwijaya, 2017)
Abstract: The objective of this quasi-experimental study was to find out whether or not there was significant difference in reading achievements between the students who were taught by using hangman game strategy and that of those who were not. The population of this study was the seventh graders of SMPN 2 Kayuagung. The samples of this study were 64 students divided into experimental and control groups. The samples were chosen using a purposive sampling method. To collect the data, written test in the form multiple choices was used and the data was analyzed statistically by using independent sample t-test. The result of independent sample t-test showed that mean difference between experimental and control groups was 14.375 at the significant level p<0.05. It meant that null hypothesis (Ho) was rejected and alternative hypothesis (Ha) was accepted. In other words, there was significant difference reading achievement between the students who were taught by using Hangman game Strategy and that of those who were not. Key words: Hangman Game Strategy, reading comprehension achievement, seventh graders